A cross sectional study of contact dermatitis among chicken farmers - Tika Nela Sirait; Helen Kartika Hasianna Sinaga (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2020)
Occupational diseases can be caused by several factors of work and environmental conditions of workers. Poor environmental conditions and worker behavior are some of the triggers for the emergence of dermatitis in workers. Contact dermatitis in chicken farm workers can be caused by exposure to chemicals from animal feed. The purpose of this study was to determine the factors that influence the occurrence of dermatitis in chicken farmworkers. This research is a quantitative study with a cross-sectional design. The population in this study was a total sample of 35 people. The results showed that there was no relationship between the use of personal protective equipment, working period, and personal hygiene with the appearance of symptoms of dermatitis in workers. However, this study found that workers who have worked for more than 12 months and practice good personal hygiene tend to avoid symptoms of dermatitis. This study provides a recommendation that the longer a person has worked, personal hygiene improvement needs to be done to avoid dermatitis.